Targeting MOR-mGluR5 heteromers reduces bone cancer pain by activating MOR and inhibiting mGluR5. (1st December 2019) - Shueb, Sarah S.; Erb, Samuel J.; Lunzer, Mary M.; Speltz, Rebecca; Harding-Rose, Catherine; Akgün, Eyup; Simone, Donald A.; Portoghese, Philip S.
Abstract: Pain is among the most common symptoms in cancer and approximately 90% of patients experience end-stage cancer pain. The management of cancer pain is challenging due to the significant side effects associated with opioids, and novel therapeutic approaches are needed. MMG22 is a bivalent ligand containing MOR agonist and mGluR5 antagonist pharmacophores joined by a 22-atom spacer. MMG22 exhibited extraordinary analgesia following intrathecal administration in a mouse model of bone cancer pain. Here, we assessed the effectiveness of systemic administration of MMG22 in reducing cancer pain and evaluated whether MMG22 displays side effects associated with opioids. Fibrosarcoma cells were injected into and around the calcaneus bone in C3H mice. Mechanical hyperalgesia was defined as an increase in the paw withdrawal frequencies (PWFs) evoked by application of a von Frey monofilament (3.9 mN bending force) applied to the plantar surface of the hind paw Subcutaneous (s.c.), intramuscular (i.m.), and oral (p.o.) administration of MMG22 produced robust dose-dependent antihyperalgesia, whose ED50 was orders of magnitude lower than morphine. Moreover, the ED50 for MMG22 decreased with disease progression. Importantly, s.c. administration of MMG22 did not produce acute (24 h) or long-term (9 days) tolerance, was not rewarding (conditioned place preference test), and did not produce naloxone-induced precipitated withdrawal or alter motor function. A possible mechanism of action of MMG22 is discussed in terms of inhibition of spinal NMDAR via antagonism of its co-receptor, mGluR5, and concomitant activation of neuronal MOR. We suggest that MMG22 may be a powerful alternative to traditional opioids for managing cancer pain. This article is part of the Special Issue entitled 'New Vistas in Opioid Pharmacology'. Highlights: Systemic administration OF MMG22 targets a MOR-mGluR5 heteromer and potently reduces bone cancer pain in mice. MMG22 does not possess adverse effects associated with traditional opioids. MMG22 activates MOR and antagonizes mGluR5.